Allan Gruchy's view of institutionalism and the foundation and early years of the Association for Evolutionary Economics - Felipe Almeida; Victor Cruz de Silva (EconomiA, 2020)
Studies on the history of economic thought of American institutionalism usually focus on the founding fathers, or pre-1930s institutionalism. The decline in importance of this school of thought during the 1930s resulted in few post-World War II studies on the history of institutionalism. However, institutionalists played a prominent role in the emergence of dissenting associations. In the late 1950s, institutionalists' dissatisfaction with the American Economic Association culminated in the Association for Evolutionary Economics (AFEE) in 1965. Allan Gruchy was a founder of the AFEE, and this paper highlights his perspective of institutionalism and how it changed over the course of his career because of his involvement in AFEE's internal affairs.
Keywords: B25; 330; Allan Gruchy; Association for Evolutionary Economics; Journal of Economic Issues; Warren Samuels; American Institutionalism